Spectrum of germline AIRE mutations causing APS-1 and familial hypoparathyroidism. Issue 1 (24th May 2022) - Cranston, Treena; Boon, Hannah; Olesen, Mie K; Ryan, Fiona J; Shears, Deborah; London, Rosemary; Rostom, Hussam; Elajnaf, Taha; Thakker, Rajesh V; Hannan, Fadil M
Abstract: Objective: The autoimmune polyendocrine syndrome type 1 (APS-1) is an autosomal recessive disorder characterised by immune dysregulation and autoimmune endocrine gland destruction. APS-1 is caused by biallelic mutations affecting the autoimmune regulator ( AIRE ) gene on chromosome 21q22.3, which facilitates immunological self-tolerance. The objective was to investigate >300 probands with suspected APS-1 or isolated hypoparathyroidism for AIRE abnormalities. Methods: Probands were assessed by DNA sequence analysis. Novel variants were characterised using 3D modelling of the AIRE protein. Restriction enzyme and microsatellite analysis were used to investigate for uniparental isodisomy. Results: Biallelic AIRE mutations were identified in 35 probands with APS-1 and 5 probands with isolated hypoparathyroidism. These included a novel homozygous p.(His14Pro) mutation, predicted to disrupt the N-terminal caspase activation recruitment domain of the AIRE protein. Furthermore, an apparently homozygous AIRE mutation, p.Leu323fs, was identified in an APS-1 proband, who is the child of non-consanguineous asymptomatic parents. Microsatellite analysis revealed that the proband inherited two copies of the paternal mutant AIRE allele due to uniparental isodisomy. Hypoparathyroidism was the most common endocrine manifestation in AIRE mutation-positive probands and >45% of those harbouring AIRE mutations had at least two diseases out of the triad of candidiasis, hypoparathyroidism, and hypoadrenalism. In contrast, type 1 diabetes and hypothyroidism occurred more frequently in AIRE mutation-negative probands with suspected APS-1. Around 30% of AIRE mutation-negative probands with isolated hypoparathyroidism harboured mutations in other hypoparathyroid genes. Conclusions: This study of a large cohort referred for AIRE mutational analysis expands the spectrum of genetic abnormalities causing APS-1.